EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION, INKUIRI TERBIMBING DAN KONVENSIONAL PADA MATERI POKOK BANGUN RUANG SISI DATAR DITINJAU DARI KREATIVITAS SISWA SMP NEGERI SE-KABUPATEN BLORA - Hanggara, Yudhi (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research aims to find out: (1) which learning model providing better learning achievement, PBI, Guided Inquiry or Conventional learning, (2) which students having better learning achievement, those with high, medium or low creativity, and (3) in each creativity level, which one providing better learning achievement, PBI, Guided Inquiry or Conventional learning model. In each learning model which students having better learning achievement, those with high, medium or low creativity. The population of research was all students of Junior High Schools throughout Blora Regency. The sample was taken using stratified cluster random sampling. The sample of research consisted of 272 students: 92 in the first experiment class, 91 in the second experiment class, and 89 in the third experiment class. The result of research showed that: (1) PBI model provided better learning achievement than the guided inquiry model did, but provided learning achievement equally good to the Conventional learning model did and Conventional learning model provided better learning achievement than the guided inquiry model did; (2) the students with high creativity had learning achievement better than those with both medium and low creativity had, and the students with medium creativity had learning achievement equally good to those with low creativity had. (3) In PBI and guided inquiry learning models, the students with high creativity had learning achievement better than those with low creativity had, the students with high creativity had learning achievement equally good to those with medium creativity had, and the students with medium creativity had learning achievement equally good to those with low creativity had. In conventional learning, the students with high creativity had learning achievement equally good to those with both medium and low creativity. At high and medium creativity level, PBI, Guided Inquiry and Conventional Model provided the equally good learning achievement. Meanwhile, at low creativity level, PBI learning model provided learning achievement equally good to the conventional learning model did, and Conventional learning model provided learning achievement better than the Guided Inquiry learning model did.Keywords: PBI, Guided Inquiry, Conventional, Creativity